A Novel Equivalent Circuit for Analysing the Effect of Local Hotspots in Micro PEM Fuel Cells. (2016) - Krishnan, Jisha R.; Ramesh, Akhil K.; Indhu, K.K.; Ramesh, P.
Abstract: The lifetime of a micro proton exchange membrane fuel cell is hugely dependent on the durability and longevity of the membrane used in the cell. An ideal membrane is expected to have its membrane impedance constant and distributed uniformly throughout. But in practice, the case is quite different. Such non uniformities in the membrane impedance will generate local hotspots in the membrane which has fatal effects such as it reduces the life time of the fuel cell. So it is imperative that we have to analyse the effects of hotspots in the fuel cell. This paper study proposes a novel equivalent circuit to analyse the impedance variations in the fuel cell membrane. The study on the effect of local hotspots in the fuel cell will lead a further research to create the rectifying methodologies for this problem.